Costos de producción de árboles de navidad (Cupressus lusitanica MILL.) en Costa Rica - Murillo, Olman (2017)
Production costs of Christmas trees (Cupressus lusitanica Mill.) in Costa Rica. Christmas tree production based on cypress (Cupressus lusitanica Mill.) started in the early 60´s in this country. An exhaustive cost data base of christmas trees production in Costa Rica, was elaborated, on the basis of a technological package for a production cycle of 2.5 years, planting initially 4444 trees.ha-1 (at a distance of 1.5 x 1.5 m) and selling 3111 trees (70%) at the end of the period. The cost structure data includes setting up 200 m of fences.ha-1 and an estimate of labor costs, which includes voluntary social security expenses. The wage cost at the II semester 2016 was established at ¢11.273.75 ($20.13 at an exchange rate of 1 US $ = C.R. ¢560). A complete production cycle requires approximately 373 wages in 3 years, some 125 wages/year, slightly below the average of a halftime farmworker. The total cost of planting one hectare was estimated at ¢6.170.786 ya que es una actividad intensiva que ofrece la posibilidad de plantar más de 4000 árboles.ha-1 (Torres y Carvajal 2012). Los autores encontraron que los problemas en la comercialización y la ausencia de organizaciones de productores, posiblemente constituyan la limitación más importante para el desarrollo del cultivo en el país. To agricultural supplies. Total cost of producing a single tree is ¢1984 ($3.54), while the selling price is above ¢7500 or 4 times the production cost. The database is statistically reliable and realistic, as related to this activity in Costa Rica. Any improvement on the technological package would be reflected as increase of productivity indicators and in production cost decrease. The use of this costs database in for future investigations is recommended